Potential of biofertilisers to improve performance of local genotype tomatoes - Puia, Carmen; Vidican, Roxana; Szabó, Gyöngyi; Stoian, Vlad (Italian Journal of Agronomy, 2017)
Complex microbial communities in the plant rhizosphere are responsible for their success in ecosystems. Supplementary inoculation of soil with mycorrhizal fungi and rhizospheric bacteria may act as a plant growth-promoting factor. The present study aims to assess the potential use of biofertilisers on tomato as a way of increasing yield and stability of root exploration area. The experiment was set up in greenhouse, regarding the evaluation of growing dynamics of plants, mycorrhization level and obtained yield. The identification of effective inoculation variants can lead to a standardisation of technologies of growing for local plant genotypes. Data analysis was performed based on the ANOVA test, followed by Tukey HSD, principal component analysis and cluster analysis in order to identify the potential of bioproducts to stimulate the development of tomato plants. Application of bacterial biofertilisers does not stimulate enough the aboveground development of plants. An antagonistic reaction is visible between exogenous mycorrhizas and those specific in soil, acting slightly different for each genotype. Mycorrhizal level in root systems is more dependent on applied biofertilisers than on analyzed genotypes. For the variants without additional fertilisers, a high level of mycorrhization is visible only after 75 days from the transplantation. Based on results we can conclude that microbial active fertilisers may represent viable solutions to increase yield capacity and root exploration area for local tomato genotypes.